The Impact of Corporate Social Responsibility on the Corporate Financial Performance: Evidence from Russian and Dutch Companies - Olga Volkova; Anastasia Kuznetsova (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2022)
This research paper aims to investigate the impact of Corporate Social Responsibility (CSR) reporting on Russian and Dutch companies’ financial performance (CFP). The theoretical framework we use is the stakeholder theory. The study applies regression analysis to obtain quantitative evidence of CSR-CFP relations. Companies’ CSR involvement is measured by reputation index - CSRhub. Return on equity ratio has been chosen as a measure of corporate financial performance. Our findings demonstrate a weak positive correlation between CSR and companies’ ROE. Moreover, the research shows the existence of a higher CSR impact on Russian companies’ financial performance comparing to the Dutch one. The results may become useful for corporate management while assessing a financial return from CSR strategies. This work also provides an alternative way for a quantitative operationalization of companies’ social performance, which is especially important for further statistical researches.